Estimasi Sumberdaya Batubara Menggunakan Metode Kriging di PT. Inti Bara Perdana, Taba Penanjung - Qurratul A’yun; Hisni Rahmi; Yudi Arista Yulanda (Pusat riset dan Inovasi Nasional, 2026)
This study aims to estimate coal resources using the kriging method at PT. Inti Bara Perdana, Taba Penanjung, Bengkulu. Geostatistical analysis was applied to evaluate spatial variability of coal quality parameters, including total moisture (TM), inherent moisture (IM), ash content (ASH), volatile matter (VM), fixed carbon (FC), and calorific value (CV). The research utilized drilling data with an average spacing of 80 meters. Variogram modeling was conducted using SGeMS software, employing spherical models to determine nugget, sill, and range parameters. The results show a low nugget effect (0%) indicating strong spatial continuity. The obtained ranges vary between 180–1296 meters depending on the parameter. Blo./ck kriging estimation was performed using block dimensions of 25 × 25 × 8 meters and a coal density of 1.3 ton/m³. The total estimated coal resource up to an elevation of 230 m is 253,500 tons. These findings demonstrate that kriging provides reliable resource estimation and supports mine planning optimization. This research contributes to improving coal resource evaluation accuracy and operational decision-making in open-pit mining.